Data Journalism Beyond Legacy Media: The case of African and European Civic Technology Organizations. Issue 9 (21st October 2019) - Cheruiyot, David; Baack, Stefan; Ferrer-Conill, Raul
Abstract: Research has paid relatively little attention to two aspects that are increasingly important in understanding data journalism as a maturing field: (a) journalism today is increasingly provided by a diverse set of actors both inside and outside of legacy media organizations, and (b) data journalism has become a global phenomenon that cannot be fully grasped within national contexts only. Our article brings both of these aspects together and investigates the roles and practices of peripheral actors in European and African contexts. We engage with research on the role of non-profits and civic technologists in journalism to interrogate further the entanglements between civic technology organizations and data journalism. Following in-depth interviews with 29 practitioners of data-driven non-profits in Europe and Africa, we conclude that practices and roles of these non-profits in relation to journalism are similar, but transcultural and contextual influences shape how they complement or expand data journalism.